Executivo e legislativo no âmbito municipal: a formação de gabinetes no município de São Paulo (1989-2012) - Garcia, Joice Godoi (2013)
The political-institutional design of Brazilian municipalities follows the logic of the federal level. Such a system has the general characteristics of the term fixed duration and proper for both the Executive and the Legislature, i.e. both are elected directly - proportional and majoritarian elections, respectively - without being subject to mutual trust as in the parliamentary system. Given the separation of powers and the conflict that literature emphasizes between the federal legislative and executive branches, the study examines the structure of the dynamics of this relationship within the municipality. Accordingly, the scope regarding the strategies adopted in the formation of the offices from 1989 to 2012 comprises 6 (six) different managements in the city of São Paulo. This study investigates the profile of political party secretariat and correspondence in terms of seats in the São Paulo Legislative, as well as the results of propositions regarding the approval of the Executive initiative. The results highlight that the distribution of portfolios does not require a support of the majority of parliament, as in the federal case. However, despite the absence of this support, virtually all executive bills that reached the plenary were approved. Thus, the study suggests that the sharing of power by appointing secretaries supporters is an important tool of the executive, but cannot be the sole guarantor of a majority coalition that explains the mayor's legislative success.